The efficiency of CFRP strengthening and repair system on the flexural behavior of RC beams constructed with different concrete compressive strength - Meyyada Y. Alabdulhady; Mohammed F. Ojaimi; Aqeel H. Chkheiwer (Results in Engineering, 2022)
This paper presents experimental investigation on the effectiveness of CFRP strengthening and repair system on the load carrying capacity, stiffness, flexural behavior, and failure mode mechanism of RC beams constructed with different concrete compressive strength (fc′). Eight RC simply supported beams were strengthened and repaired with one layer of CFRP composite and tested experimentally under flexural load. The beams were built with varying the concrete compressive strength (fc′) value of (21.1, 36.1, 48.2, and 68.5) MPa, to demonstrate low, normal, and high strength. The results obtained in this work revealed that the performance of the CFRP composite material was inversely correlated to the concrete compressive strength in repaired beams while a proportion relation was observed in strengthened beams only with low to normal concrete strength. Finally, reasonable agreement between the estimated bending moment capacities for strengthened beams (based on the ACI 440.2R-17 provision) and the experimental results within ±16% were obtained.